2020
DOI: 10.1039/c9nj05142b
|View full text |Cite|
|
Sign up to set email alerts
|

Sunlight assisted degradation of a pollutant dye in water by a WO3@g-C3N4 nanocomposite catalyst

Abstract: A series of WO3@g-C3N4 nanocomposites were prepared by following a facile, cost-effective chemical rote and characterized by different techniques. They are promising photocatalyst with high potential for solar light harvesting and environmental remediation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 81 publications
1
20
0
Order By: Relevance
“…Figure 15e displays the PL emission peak of the bulk g-C 3 N 4 and 18.6 wt % WO 3 /g-C 3 N 4 hybrid composite [254]. The result demonstrates that the intensity of the composites' PL peak at ~440 nm is lower than that of the pure g-C 3 N 4 [255][256][257]. The PL spectra revealed that WO 3 apparently suppresses the photoinduced electron-hole recombination in the WO 3 /g-C 3 N 4 composites and confirms the Z-scheme interface contact [258].…”
Section: Cheng Et Al Also Demonstrated the Insignificant Deactivation...mentioning
confidence: 98%
“…Figure 15e displays the PL emission peak of the bulk g-C 3 N 4 and 18.6 wt % WO 3 /g-C 3 N 4 hybrid composite [254]. The result demonstrates that the intensity of the composites' PL peak at ~440 nm is lower than that of the pure g-C 3 N 4 [255][256][257]. The PL spectra revealed that WO 3 apparently suppresses the photoinduced electron-hole recombination in the WO 3 /g-C 3 N 4 composites and confirms the Z-scheme interface contact [258].…”
Section: Cheng Et Al Also Demonstrated the Insignificant Deactivation...mentioning
confidence: 98%
“…Based on the above hypothesis, graphitic carbon nitride (g-C 3 N 4 ) might be a suitable compound for coupling with the ZnO/CuO composite because of its low cost and large-scale manufacturing, unique electronic and optical properties, good chemical and thermal stability, facile preparation, and non-toxicity [17,18]. In addition, the photocatalytic activity of g-C 3 N 4 -related composites has been extensively studied [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the photocatalytic activity of g-C 3 N 4 -related composites has been extensively studied [19][20][21][22][23]. However, the photocatalytic efficiency towards pollutant degradation of pristine g-C 3 N 4 is low due to its quick e − -h + pair recombination ability [18,24]. Therefore, to counteract this drawback, various methods have been applied in attempts to increase the visible light photocatalysis, particularly coupling with other semiconductors or metals, non-metal doping, control of morphology, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional techniques like sedimentation, oxidation by chemical methods, ltration and coagulations have many drawbacks due to the formation of various byproducts, and the associated energy and cost intensive methods 2,3 . Hence, nanoparticles with high photocatalytic properties are being explored as a solution to eliminate harmful pollutants from water bodies.…”
Section: Introductionmentioning
confidence: 99%